Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1039/d0ra05409g
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced charge storage properties of ultrananocrystalline diamond films by contact electrification-induced hydrogenation

Abstract: The enhanced charge storage characteristics of ultrananocrystalline diamond caused by contact electrification-induced hydrogenation was demonstrated by using atomic force microscopy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 55 publications
0
1
0
Order By: Relevance
“…To obtain a hydrogen-terminated surface, the activation of hydrogen atoms is performed usually by hot filament (HF) process [ 18 , 19 , 20 ], microwave (MW) process [ 21 , 22 , 23 ] or radio frequency (RF) process [ 22 ]. Recently, it has also been shown that contact electrification-induced hydrogenation method results in effective hydrogen termination of nanodiamond surface [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…To obtain a hydrogen-terminated surface, the activation of hydrogen atoms is performed usually by hot filament (HF) process [ 18 , 19 , 20 ], microwave (MW) process [ 21 , 22 , 23 ] or radio frequency (RF) process [ 22 ]. Recently, it has also been shown that contact electrification-induced hydrogenation method results in effective hydrogen termination of nanodiamond surface [ 24 ].…”
Section: Introductionmentioning
confidence: 99%